Pengaruh Kesadaran Merek, Komitmen Laman Akun Merek, dan Pengalaman Pelanggan Terhadap Electronic Word Of Mouth Serta Dampaknya Terhadap Minat Beli Ulang Konsumen Patroli Kopi, Karawang, Jawa Barat - Zainal Abidin (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2020)
The objective of this research is to study and understand the relationship between Brand Awareness, Brand Page Commitment, Customer Experience, e-WOM, and those impact to Repurchase Intention in the coffee shop market. The study samples 100 consumers of Patroli Kopi in Karawang, West Java, Indonesia as the case study. Data analysis for this study was conducted using SPSS (Statistical Package for the Social Sciences) software. The analysis used descriptive statistics such as mean, frequency, percentage, and standard deviation, as well as path analysis to facilitate meaningful analysis. The findings indicate that each independent variable partially has a consequential effect in both E-WOM and Repurchase Intention. Contrary, Brand Page Commitment variable is partially shown minor relations effect toward E-WOM, as well as E-WOM, partially has insignificant relations to Repurchase Intention. Nevertheless, the following variables which consist of Brand Awareness, Brand Page Commitment, Customer Experience simultaneously shown a significant effect on E-WOM. Moreover, the significant factor simultaneously can be determined through variable path analysis of Brand Awareness, Brand Page Commitment, Customer Experience, and E-WOM towards Repurchase Intention.